ESTRUS INDUCTION AND FERTILITY FOLLOWING SINGLE DOSE OF PROSTAGLANDIN F 2 ALPHA IN CROSSBRED COWS AND HEIFERS - PATIL, S R; PAWSHE, C H (The Indian Journal of Animal Reproduction, 2011)
The present study was conducted on 12 crossbred cows and heifers. These selected animals were dividedinto two Groups, comprising of 8 cows in Group-I and 4 heifers in Group-II and treated with single dose of Lulalyse(PGF 2alpha , Dinoprost thromethamine 25 mg) intramuscularly
Keywords: Cattle; Estrus synchronization; Fertility response